Trabalho de diplomação como mecanismo de interação universidade-empresa: transferência de tecnologia - Hruschka, Janete (2005)
Innovation strategies and technology transfer between enterprises and learning institutions through interaction mechanisms are being used so as to implement technological innovations. The work means to propose a new mechanism of University-Enterprise interaction, through the analyses of graduation work results developed in partnership with enterprises which contributed for improvements in processes, products or services of their own. It is an exploratory research that, due to the technical procedures adopted, can be characterized as a case study. The data were collected within two stages. In the first, relative to the documents, the texts of the graduation works were analyzed developed by their authors (individually or in group), and accomplished a classification and grouping of the works developed in partnership with enterprises. In the second stage they were located the enterprises and the supervisors that worked directly with the students in the development of graduation work and the advisors of the projects in the Institution of Teaching, and the data were collected through semi-structured individual interview and questionnaire. The obtained results appear for the viability of partnership of teaching institutions and companies, looking for committees the resolution of existent problems in the productive section through development of TD. The constant search for technological updatings is determining a relationship among the ones that develop the technology with the ones that will use her. And that relationship is denominated of technology transfer.